The morphometric conceptin modern botany (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The basic directions of plant morphometrics (phytomorphometrics) development, as a branch of botany, engaged in the quantitative description of appropriateness of a structure and development of plant individuals and their structural parts are considered. The main attention is given to the new and promising directions: allometry, correlation adaptometry, fluctuating asymmetry and to processes of growth and formbuilding in plants. The critical estimation of some morphometrics methods is given.
Keywords: plant morphometrics, growth, formbuilding, allometry, fluctuating asymmetry, correlation.